Pengaruh Gaya Hidup dan Kualitas Produk Terhadap Keputusan Pembelian Sepatu Converse: Studi Pada Mahasiswa D4 Manajemen Pemasaran Jurusan Administrasi Niaga Politeknik Negeri Malang - Safrida Azzahra; Yulis Nurul ‘Aini (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Converse shoes are foreign sneakers brand that is considered a classy product that is still a favorite of many people in the world, including in Indonesia. Consumers purchase a product that was in line with their tastes and lifestyle., and to influence consumers to make purchase, Converse offers good quality product. The goal of this study is to understand how lifestyle and product quality affect consumers' decisions to purchase Converse sneakers. 65 D4 Marketing Management students at Malang State Polytechnic who had purchased Converse shoe goods participated in this quantitative study. Data was gathered utilizing a questionnaire-based approach. To choose responders, the Accidental Sampling method was applied. Testing hypotheses and multiple regression analysis are two techniques for data analysis. Study findings on the relationship between lifestyle and product quality and purchase decisions indicate that Fcount>Ftable, or 42.517>3.15, with a coefficient of determination of 0.565. The study's findings indicate that lifestyle and product quality account for 56.5% of purchase decisions, with other factors accounting for 43.5% of decisions that were not examined. According to this study, judgments on what to buy are influenced by both product quality and lifestyle. It is also expected that Converse companies can pay attention to consumer lifestyles and maintain the quality of Converse products and continue to innovate to stay superior to other shoe brands.